2020
DOI: 10.1186/s12906-020-2819-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin-3-glucoside activates Nrf2-antioxidant response element and protects against glutamate-induced oxidative and endoplasmic reticulum stress in HT22 hippocampal neuronal cells

Abstract: Background: Cyanidin-3-glucoside (C3G), a major anthocyanin present in berries, exhibits a strong antioxidant and has been shown to possess a neuroprotection. Prolonged exposure to glutamate will lead to oxidative damage and endoplasmic reticulum stress which could play a key detrimental role in the development of neurodegenerative disorders (NDs). In the present study, we investigated the neuroprotective effect and underlying mechanisms of C3G on the reduction of oxidative/ER stress-induced apoptosis by gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 59 publications
5
46
0
Order By: Relevance
“…Similarly, LRE also induced a decrease in PolyQ40 aggregation that is related to the neurodegenerative diseases including Huntington’s disease and other polyglutamine diseases [ 55 ]. Our findings agree with several previous studies about phenolic compounds that have been found in plants or natural products and reported their effectiveness in preventing many diseases including neurodegenerative diseases [ 19 , 43 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Only LRE exerted the neuroprotective effect both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, LRE also induced a decrease in PolyQ40 aggregation that is related to the neurodegenerative diseases including Huntington’s disease and other polyglutamine diseases [ 55 ]. Our findings agree with several previous studies about phenolic compounds that have been found in plants or natural products and reported their effectiveness in preventing many diseases including neurodegenerative diseases [ 19 , 43 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Only LRE exerted the neuroprotective effect both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we report, for the first time to our knowledge, the neuroprotection of LR extracts against glutamate-induced oxidative stress in HT22 cells and neurotoxicity in C. elegans . In this cell line, we induced oxidative stress by using 5 mM glutamate which has been reported to reduce approximately 50% of the cells [ 19 , 43 ]. Interestingly, we found that only LRE prevented cells from undergoing apoptosis after cotreatment by using Annexin V/PI straining that interacts strongly and specifically with exposed phosphatidylserine (PS), the marker of apoptosis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with grape-derived polyphenols from a variety of sources, including CGJ, in patients suffering from mild age-related cognitive decline, resulted in benefits in working memory and improved verbal learning 54 , 55 . The anti-inflammatory and anti-oxidant properties of FDP-derived metabolites, demonstrated in vitro, in vivo using models of stress 15 , 16 , 46 , 47 , have been recapitulated in preclinical and clinical trials 53 55 . Our current study, along with these preclinical successes demonstrate that FDP may serve as a potential therapeutic for addressing the immunological pathologies associated with mood disorders and cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…While our studies did not directly examine markers of mitochondrial oxidative stress, treatment with GSPE (a component of FDP) preserves memory function in a mouse model of vascular dementia through alleviation of oxidative stress 45 . Individual metabolites that potently inhibited the production of IL-1β in vitro, including MG and CG, upregulate superoxide dismutases and phase II enzymes such as Glutathione S-transferases, while inhibiting the expression of xanthine oxidase 46 , 47 . Metabolites derived from FDP may have pleiotropic effects in the preservation of cognitive function during stress including the inhibition of inflammasome activity as well as amelioration of oxidative stress, thus inhibiting the activation of microglia 48 .…”
Section: Discussionmentioning
confidence: 99%